Al-Fārabī: Ḥayātuhu al-‘Aqliyah wa Maṣādiruhu al-Falsafiyah - â€˜Abd al-Muâ€˜á¹Ä«, Muá¸¥ammad Fakhr al-DÄ«n (Jurnal Usuluddin, 2004)
This article describes the personality, life and works of al-Farabi, one of the famous philosophers. It also discusses the Islamic and Greek sources from which al-Farabi built up his philosophical ideas. The article tries to show to what extent he has been influenced by the sources mentioned.